Spatial Structure Analysis of Benthic Ecosystem Based on Geospatial Approach at Parang Islands, Karimunjawa National Park, Central Java, Indonesia - Muhamamd Helmi; Afrina Aysira; Munasik Munasik; Anindya Wirasatriya; Rikha Widiaratih; Raden Ario (Indonesian Journal of Oceanography, 2020)
This research examines the spatial structure of live coral based on its patches on a geospatial data. Spatial structure is a part of the landscape ecology approach that has been applied on terrestrial and applied on marine ecosystems on this research. It is including Mean Shape Index (MSI), Number of Patches (NumP), Mean Patch Size (MPS), Total Seascape Area (TLA) and Class Area (CA). Live coral patches were extracted based on GeoEye-1 satellite image with several tasks, such as ortho-rectification, atmospheric calibration, water column correction; Lyzenga transform and supervised classification. A field survey was done in 2015 - 2016 with 38 verification sites and 16 sites of manta tow. Live coral patches produced a significant accuracy (overall accuracy=84.1%, user accuracy= 81.8%, producer accuracy = 90%, and Kappa Index k = 0.81%). Live coral was found 35% (CA: 201.99 ha) of seascape TLA area 814.19 ha and spread over a large number of patches (NumP: 5613-21087 patches). The live coral had a mean shape index (MSI) between 1.23 to 1.25 and the average size of patches (MPS) between 0.0029 - 0.0082. This approach could be applied to reef ecosystems and becomes a baseline data to anticipate future damage.